Properties and sensory acceptability of creatine-fortified foods using ultra-micronized creatine monohydrate – the KREAFOOD Project - Julián Quintero-Quiroz; Sebastian Botero-Ramirez; Simon Jaramillo-Caro; Natalia Zuluaga; Diego A. Bonilla (Journal of the International Society of Sports Nutrition, 2025)
Background Creatine, widely recognized for its benefits in sports nutrition, is being explored in food applications to diversify its use and develop functional products. Here, we present preliminary data as part of The KreaFood Project, a research and innovation project conceptualized by the DBSS Research Division and co-developed with the Center for Advanced Studies in Nutrition and Food – CESNUTRAL at Universidad CES.Methods We assessed the potential of KreaFood products using Creavitalis®, an ultra-micronized creatine monohydrate powder, for developing creatine-fortified beverages and solid foods. Its performance was compared to regular creatine monohydrate in two food matrices: a mocaccino premix and a pancake premix. To prepare the mocaccino, 30 g (10% creatine) of the KreaFood premix was dissolved in 300 mL of warm water and stirred until homogeneous. For the solid food, 35 g of the KreaFood pancake premix (containing 10% creatine) was dissolved in 60 mL of milk and then cooked over low heat for one minute on each side or until golden brown. Quantitative descriptive sensory testing was performed on the KreaFood products using a double-blind panel of 15 trained evaluators. Additionally, rheological analysis was conducted for the mocaccino, while texture profile analysis (TPA) was used to assess the pancakes. We assessed the potential of KreaFood products using Creavitalis®, an ultra-micronized creatine monohydrate powder, for developing creatine-fortified beverages and solid foods. Its performance was compared to regular creatine monohydrate in two food matrices: a mocaccino premix and a pancake premix. To prepare the mocaccino, 30 g (10% creatine) of the KreaFood premix was dissolved in 300 mL of warm water and stirred until homogeneous. For the solid food, 35 g of the KreaFood pancake premix (containing 10% creatine) was dissolved in 60 mL of milk and then cooked over low heat for one minute on each side or until golden brown. Quantitative descriptive sensory testing was performed on the KreaFood products using a double-blind panel of 15 trained evaluators. Additionally, rheological analysis was conducted for the mocaccino, while texture profile analysis (TPA) was used to assess the pancakes.Results Creavitalis® was characterized by its smaller particle size and thermal stability, which facilitates more homogeneous dispersion and enhanced sensory texture in fortified food applications. In the mocaccino, sensory analysis revealed significant differences in granularity (P = 0.049), with lower granularity observed in the KreaFood product. In fact, preference for the KreaFood mocaccino was 46.7% (7/15), making it the option when a sweeter and creamier profile with a good chocolate aroma is desired. For pancakes, TPA tests showed that the KreaFood pancake exhibited higher cohesiveness (0.8255), resulting in a more uniform and smoother texture. Conversely, other commercial creatines displayed greater hardness (187.739 N) and gumminess (177.44), which translated into a less favorable sensory perception due to increased granularity. The superior cohesiveness observed in the KreaFood pancake product was attributed to its ability to integrate efficiently into the solid matrix during cooking. Our pancake premix was preferred by 53.3% (8/15) and demonstrated a more favorable sensory profile in terms of foaminess, odor intensity, and sweet taste, which are attributes generally desirable in solid foods.Conclusion The KreaFood creatine-fortified foods using ultra-micronized creatine monohydrate (Creavitalis®) demonstrated significant advantages by improving cohesiveness and reducing perceived granularity, thereby optimizing the sensory quality of the final product. The KreaFood project continues with validation in larger samples and testing of new applications in cappuccino, kumis, cereal bars, and ice cream.Disclosures DAB serves as the Scientific and Managing Director of KreaFood, an R&D&I project, and is a member of the “Creatine for Health” scientific advisory board for Alzchem Group AG. He leads the CREAS project by DBSS (available at: http://CREAS.pro/).